2018
DOI: 10.1007/s00276-018-2015-3
|View full text |Cite
|
Sign up to set email alerts
|

A simple method to locate mandibular foramen with cone-beam computed tomography and its relevance to oral and maxillofacial surgery: a radio-anatomical study

Abstract: This study suggested the '40% rule' to locate the 'target area' for IAN block and 'safety zone' for ramus osteotomies approached extra-orally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
29
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(38 citation statements)
references
References 21 publications
6
29
1
2
Order By: Relevance
“…The findings of this study indicated an absolute positional bilateral symmetry of the MC and bone thickness in the region of MSSO, and this is in agreement with previous studies (7,8,11). As for gender, gender did not always lead to a significant variation in distances measured in this study, and this is in agreement with recent studies (7,11) and with the fact that genetic and environmental factors may also influence bone size and thickness (8,19).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The findings of this study indicated an absolute positional bilateral symmetry of the MC and bone thickness in the region of MSSO, and this is in agreement with previous studies (7,8,11). As for gender, gender did not always lead to a significant variation in distances measured in this study, and this is in agreement with recent studies (7,11) and with the fact that genetic and environmental factors may also influence bone size and thickness (8,19).…”
Section: Discussionsupporting
confidence: 93%
“…The findings of this study indicated an absolute positional bilateral symmetry of the MC and bone thickness in the region of MSSO, and this is in agreement with previous studies (7,8,11). As for gender, gender did not always lead to a significant variation in distances measured in this study, and this is in agreement with recent studies (7,11) and with the fact that genetic and environmental factors may also influence bone size and thickness (8,19). However, measurements recorded in this study were significantly variable according to age and in concordance with the fact that the position of the MC in relation to other landmarks is not constant and affected by imbalanced growth and remodeling occurred with advancing age, characterized by thickening of the buccal and inferior aspects of mandibular bone and resorption of the superior and lingual aspects moving the MC in a superior and lingual direction and leaving a decreased amount of cancellous bone, and shorter ramus and mandibular posterior region (8,20,21).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…According to [8] the mandibular foramen cannot be palpated clinically and its location is variable at the medial surface of the mandibular ramus. Nevertheless, determining its exact location is very important to the oral and maxillofacial surgeon for the relevant anesthetic and surgical ramus procedures.…”
Section: Introductionmentioning
confidence: 99%